The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s00335-015-9614-7
|View full text |Cite
|
Sign up to set email alerts
|

The GPSM2/LGN GoLoco motifs are essential for hearing

Abstract: The planar cell polarity (PCP) pathway is responsible for polarizing and orienting cochlear hair cells during development through movement of a primary cilium, the kinocilium. GPSM2/LGN, a mitotic spindle-orienting protein associated with deafness in humans, is a PCP effector involved in kinocilium migration. Here, we link human and mouse truncating mutations in the GPSM2/LGN gene, both leading to hearing loss. The human variant, p.(Trp326*), was identified by targeted genomic enrichment of genes associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 56 publications
1
47
0
Order By: Relevance
“…LGN and Gαi colocalize at the tips of stereocilia in the first row Insc-LGN-Gαi are planar polarized in murine cochlear post-mitotic HCs from embryonic day (E) 15.0 (Bhonker et al, 2016;Ezan et al, 2013;Tarchini et al, 2013), labeling and expanding the bare zone (Tarchini et al, 2013). At E16.5, we found that LGN and Gαi become enriched in a second apical compartment: the tips of developing stereocilia in inner hair cells (IHCs) (Fig.…”
Section: Resultsmentioning
confidence: 90%
See 4 more Smart Citations
“…LGN and Gαi colocalize at the tips of stereocilia in the first row Insc-LGN-Gαi are planar polarized in murine cochlear post-mitotic HCs from embryonic day (E) 15.0 (Bhonker et al, 2016;Ezan et al, 2013;Tarchini et al, 2013), labeling and expanding the bare zone (Tarchini et al, 2013). At E16.5, we found that LGN and Gαi become enriched in a second apical compartment: the tips of developing stereocilia in inner hair cells (IHCs) (Fig.…”
Section: Resultsmentioning
confidence: 90%
“…LGN or Gαi inactivation leads to disorganization of stereocilia distribution at the HC apical membrane (Bhonker et al, 2016;Ezan et al, 2013;Tarchini et al, 2013), which we interpreted to be the result of defective bare zone specification and expansion (Tarchini et al, 2013). Prompted by LGN-Gαi localization at their tips, we undertook a detailed analysis of stereocilia morphology during development.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations